The Median Voter Hypothesis, Income Inequality and Income Redistribution: An Empirical Test with the Required Data - Branko Milanović (Luxembourg Income Study (LIS), 2000)
The median voter hypothesis has been central to an extensive literature on consequences of income distribution. For example, it has been proposed that greater inequality is associated with lower growth, because of the greater redistribution that is sought by the median voter when income distribution is less equal. There have however been no proper tests of the median-voter hypothesis concerning redistribution, because of previous absence of data on factor income distribution (that is, incomes before taxes and transfers) across households, and thus on the gains by poorer households from redistribution. The study reported in this paper is based on the required data, with 79 observations drawn from household budget surveys from 24 democracies. The results strongly support the conclusion that countries with greater inequality of factor income redistribute more to the poor. This is so even when we control for the share of the elderly in the population and for pension transfers. The evidence that the median-voter hypothesis adequately describes the collective-choice mechanism is however considerably weaker. Although middle-income groups gain more/or lose less through redistribution in countries where initial (factor) income distribution is more unequal, this regularity is all but lost when, by excluding pensions, we look only at explicit redistributive social transfers from which the middle classes contemporaneously gain little. This leaves us searching for alternative explanations: do middle-classes gain from transfers in the long-run even if not contemporaneously, or is the median voter hypothesis, based on direct democracy, a proper representation of the mechanisms of collective-decision making in representative democracy?
Keywords: 330; Medianwähler-Modell; Einkommensverteilung; Neue Wachstumstheorie; Einkommensumverteilung; Welt